Dendrimer-modified gold nanorods as a platform for combinational gene therapy and photothermal therapy of tumors - Lili Ye; Yaoming Chen; Jizong Mao; Xiaotian Lei; Qian Yang; Chunhui Cui (Journal of Experimental & Clinical Cancer Research, 2021)
Abstract Background The exploitation of novel nanomaterials combining diagnostic and therapeutic functionalities within one single nanoplatform is challenging for tumor theranostics. Methods We synthesized dendrimer-modified gold nanorods for combinational gene therapy and photothermal therapy (PTT) of colon cancer. Poly(amidoamine) dendrimers (PAMAM, G3) grafted gold nanorods were modified with GX1 peptide (a cyclic 7-mer peptide, CGNSNPKSC). The obtained Au NR@PAMAM-GX1 are proposed as a gene delivery vector to gene (FAM172A, regulates the proliferation and apoptosis of colon cancer cells) for the combination of photothermal therapy (PTT) and gene therapy of Colon cancer cells (HCT-8 cells). In addition, the CT imaging function of Au NR can provide imaging evidence for the diagnosis of colon cancer. Results The results display that Au NR@PAMAM-GX1 can specifically deliver FAM172A to cancer cells with excellent transfection efficiency. The HCT-8 cells treated with the Au NR@PAMAM-GX1/FAM172A under laser irradiation have a viability of 20.45%, which is much lower than the survival rate of other single-mode PTT treatment or single-mode gene therapy. Furthermore, animal experiment results confirm that Au NR@PAMAM-GX1/FAM172A complexes can achieve tumor thermal imaging, targeted CT imaging, PTT and gene therapy after tail vein injection. Conclusion Our findings demonstrate that the synthesized Au NR@PAMAM-GX1 offer a facile platform to exert antitumor and improve the diagnostic level of tumor.